In Silico Study of Alkaloid Compounds from Sida rhombifolia (Sidaguri) as Antimalarial Agents Targeting Plasmodium falciparum Dihydrofolate Reductase - Arfansyah, Arfansyah; Sepyana, Anisa; Bahrun, Bahrun; Artasasta, Muh Ade; Rasyid, Herlina (Indonesian Journal of Chemistry, 2025)
Malaria, caused by the Plasmodium parasite, represents a significant global health challenge, with approximately 229 million cases reported in 2020. Current treatments include artemisinin-based combination therapy; however, drug resistance poses serious issues. Natural products, including alkaloids from Sida rhombifolia, particularly cryptolepine, effectively inhibit Plasmodium falciparum through DNA intercalation. Research indicates that mutations in the PfDHFR enzyme of P. falciparum contribute to drug resistance, highlighting the urgent need for new inhibitors. A literature review combined with SwissADME, toxicology predictions, and molecular docking methods identified 11-cryptolepine carboxylic acid (B1) and N-trans-feruloyl tyramine (B11) as potential new inhibitors. The compounds exhibited binding energies of −7.22 and −8.41 kcal/mol, which are close to the native ligand (−7.31 kcal/mol). Additionally, they demonstrate favorable drug-likeness properties, indicating their potential as viable candidates for drug development. The molecular dynamics simulation for 100 ns was conducted to observe molecular interactions in a specific system dynamically. It was found that ligand B1 has better stability compared to ligand B11. This compound demonstrates significant potential for advancing malaria treatment strategies. Further research and clinical evaluation are warranted to fully realize their potential and translate these findings into effective clinical interventions for combating malaria globally.